Air—water model studies of cocurrent flow into and along a PWR hot leg to the steam generator - Gardner, G.C. (Nuclear engineering and design, 1989)
An experimental study is made of the cocurrent flow of air and water at atmospheric pressure from a reactor vessel into and along an approximately ninth-scale replica of the Sizewell ‘B’ PWR hot leg to the steam generator. A flow regime map of conditions in the hot leg is presented. The water interface level in the reactor vessel as a function of the flowrates is in agreement with a recent theory developed by the author. The same theory predicts the level in the hot leg when discharging two phases through a horizontal break and is in agreement with the results of other workers on this subject for the discharge of air and water up to a pressure of 5 bar and of steam and water up to a pressure of 62 bar. Results on the water level in the hot leg are correlated empirically but, for lower flowrates, the results are in approximate agreement with a theory for the onset of flooding.